*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer: 440 ft^2
Explanation:
I hope this helped!
<!> Brainliest is appreciated! <!>
- Zack Slocum
*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆*――*☆**☆*――*☆*――*☆*――*☆
Answer: -10
Step-by-step explanation:
Simplifying
-3(y + 5) = 15
Reorder the terms:
-3(5 + y) = 15
(5 * -3 + y * -3) = 15
(-15 + -3y) = 15
Solving
-15 + -3y = 15
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '15' to each side of the equation.
-15 + 15 + -3y = 15 + 15
Combine like terms: -15 + 15 = 0
0 + -3y = 15 + 15
-3y = 15 + 15
Combine like terms: 15 + 15 = 30
-3y = 30
Divide each side by '-3'.
y = -10
Simplifying
Division and multiplication
Answer:
[x+6y+2z][x²+(6y)²+(2z)²-6xy-12yz-2xz]
Step-by-step explanation:
x³+216y³+8z³-36xyz
x³+(6y)³+(2z)³-3×6×2×xyz
As we know
a³+b³+c³-3abc=(a+b+c)(a²+b²+c²-ab-bc-ca)
Let a=x
b=6y
c=2z
Now.
[x+6y+2z][(x²+(6y)²+(2z)²-x×6y-6y×2z-x×2z]
[x+6y+2z][x²+(6y)²+(2z)²-6xy-12yz-2xz]
Answer:
-7 - 3a = 1 – 4a
Step one: Add 4a to -3a
-7 + a = 1
Step two: Add 7 to 1
A = 8
You're done! A=8 for this problem!
Hopefully this helps! Feel free to mark brainliest!